(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Authors elucidates the problems of syntaxonomy of Cakiletea maritimae and Ammophiletea in Europe. A comparative characteristics and classification of syntaxa mentioned are given.